PENGARUH PEMBERIAN MAKANAN TAMBAHAN PEMULIHAN BERBAHAN DASAR LOKAL TERHADAP PERUBAHAN BERAT BADAN BALITA GIZI KURANG - Yosefina Nelista; Pembronia Nona Fembi (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
Malnutrition is a health disorder due to a lack or imbalance of nutrients needed for growth, thinking activities and all things related to life. One of the efforts made to help meet the nutritional needs of malnourished children under five is the Recovery Supplementary Feeding (PMT) program. The purpose of this study was to analyze whether the effect of supplementary feeding with local ingredients on changes in body weight of undernourished children under five. The type of research used is pre-experimental research design with one group pre and post-test design. This research was conducted in the working area of the Nanga Public Health Center. The population in this study were all underweight children under five in the working area of the Nanga Health Center as many as 30 people, the sampling technique in this study was total sampling. Data processing is done by editing, coding, entry, tabulating and cleaning. Data analysis in this study was bivariate with Paired Test. The results showed that there was an effect of providing local-based supplementary food to changes in body weight of undernourished children under five as indicated by a p value of 0.000 < 0.05, with a pre-test Mean value (9.744) < Post-test Mean (10.022). and the value of t-count (7.409) > t-table (2005). Based on these results, it can be concluded that the provision of local-based supplementary food is effective in increasing the weight of undernourished children under five.